Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/00016489.2018.1508888
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of hearing preservation for residual hearing with longer cochlear implant electrodes

Abstract: Background: Hearing preservation is thought to be achievable following atraumatic surgery with thin cochlear implant electrodes; therefore, the surgical approach and implant electrode design are crucial considerations. Objective: To assess the feasibility of hearing preservation with long electrodes for patients meeting the criteria for conventional cochlear implantation. Methods: One hundred and two patients (132 ears) who underwent cochlear implant surgery were analyzed. Inclusion criteria included measurabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…This phenomenon was observed in another study using shorter electrode arrays (20 mm) [14], so that irrespective of the length of inserted electrode arrays, the intrinsic structural vulnerability of the basal- apical turn may potentially explain this. Additionally, the HP outcomes were independent of the electrode length (24 mm vs. 28 mm vs. 31.5 mm), which was consistent with the findings that there were no differences in HP score among the insertion depth angles in our and other previous reports [7,8]. Conversely, Suhling et al reported that 20-or 24-mm electrodes resulted in better HP than did those 28 mm in length [15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This phenomenon was observed in another study using shorter electrode arrays (20 mm) [14], so that irrespective of the length of inserted electrode arrays, the intrinsic structural vulnerability of the basal- apical turn may potentially explain this. Additionally, the HP outcomes were independent of the electrode length (24 mm vs. 28 mm vs. 31.5 mm), which was consistent with the findings that there were no differences in HP score among the insertion depth angles in our and other previous reports [7,8]. Conversely, Suhling et al reported that 20-or 24-mm electrodes resulted in better HP than did those 28 mm in length [15].…”
Section: Discussionsupporting
confidence: 92%
“…As described in our previous report [7], we demonstrated that a younger age at the time of implantation led to statistically better HP, indicating that the implant age is one of the key predictors influencing residual hearing in CI surgery (Table 3). On the other hand, we did not find that HP was associated with pre-operative LFA or CDL, which contradicts some previous studies that suggest there is a positive impact on post-operative hearing [8].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The role of material and surface properties on foreign body reactions and impedances is not fully understood and needs further investigation. However, hearing preservation in the lower frequencies is achieved even by the use of longer electrodes from the same manufacturer that has been used in the present study (26). Therefore, it seems unlikely that the electrode array has elicited a strong foreign body reaction.…”
Section: Discussionmentioning
confidence: 68%
“…Regular CI has been applied for patients with insufficient amplification by hearing aids (Miyagawa et al, ) and, for the patients with residual hearing, EAS devices are a good therapeutic option (Usami et al, ; Moteki et al, , ). A significant portion of EAS patients possess CDH23 mutations (Moteki et al, , ; Yoshimura et al, submitted). Therefore, it is extremely important to perform atraumatic CI surgery to preserve residual hearing for this particular category of patients.…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%